EFFECT OF ACUTE EXERCISE FOR GENITAL SEXUAL AROUSAL IN FEMALES - Therene Roteno; Nila Wahyuni (Sport and Fitness Journal, 2023)
Background: Studies to investigate the relationship between exercise and sexual function are limited. The physiological mechanism during exercise in affecting female sexual function, especially genital sexual arousal is assessed. Methods: We performed literature searching in several online databases such as PubMed, EMBASE, CENTRAL, and Google Scholar. We performed searching using keywords (acute exercise) AND (sexual arousal) to find eligible literature. We create a narrative review to discuss the effect of acute exercise on genital sexual arousal. Discussion: Acute exercise is reported to have an influence on the expression of hormones such as cortisol, estrogen, prolactin, oxytocin, and testosterone. The cortisol, estrogen, and testosterone increase genital sexual arousal by direct effect. Genital sexual arousal occurs due to the increased thickness of the vaginal epithelium, increase vaginal lubrication, and increase genital sensations. Prolactin and oxytocin influence genital sexual arousal by indirect effect. Acute exercise also increases the activation of the sympathetic nervous system which leads to increased genital sexual arousal in females. The increased sympathetic tone leads to increase cardiac output and vasodilatation. Vasodilatation causes an increase in blood flow to the genital organ. Conclusion: Acute exercise increases genital sexual arousal in females via hormonal and sympathetic nervous system pathways. Keywords: acute exercise; genital; hormonal; sexual arousal, sympathetic